2012
DOI: 10.1016/s0034-7094(12)70169-1
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and the Immune System: Clinical Relevance

Abstract: Although several studies point to an immunosuppressive effect of opioids, the clinical relevance of these observations remains uncertain and only serves as a prerequisite for further investigations in this area. Definitive recommendations for the use of opioids in various situations of clinical practice regarding the immunological consequences of these drugs still cannot be provided until the present moment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Opioids are known to restrict the body’s natural defenses against aspiration and lung infection or inflammation, via cough suppression and bronchoconstriction . Although clinically significant human studies have largely been limited, animal and cellular studies have also shown increases in rejection‐specific immunologic markers, and signs of immunosuppression after opioid exposure . Finally, chronic pain can be a symptom of rejection, suggesting that chronic opioid use is a marker for rejection associated pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opioids are known to restrict the body’s natural defenses against aspiration and lung infection or inflammation, via cough suppression and bronchoconstriction . Although clinically significant human studies have largely been limited, animal and cellular studies have also shown increases in rejection‐specific immunologic markers, and signs of immunosuppression after opioid exposure . Finally, chronic pain can be a symptom of rejection, suggesting that chronic opioid use is a marker for rejection associated pain.…”
Section: Discussionmentioning
confidence: 99%
“…Lung function may also be adversely affected by respiratory depression and bronchoconstriction caused by opioids . Finally, opioids have been shown to increase autoimmunity factors, while decreasing the body’s ability to fight infection in animal and cellular models . Limited studies of short‐term opioid use effects on immunity in humans have revealed mixed results regarding clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently much attention has been emphasised on opioids and its impact on the immune system 13,14 . Opioids have been shown to modulate immune function by direct effects on cells of the immune system and indirectly via centrally mediated neuronal mechanisms 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact some study suggests that while heroin negatively affects both innate and acquired immunity, patients on long-term methadone treatment seem to have preserved immune functioning [20]. The clinical relevance of this immunomodulation remains uncertain [21]. …”
Section: Introductionmentioning
confidence: 99%